Regime internacional de mudanças climáticas: ações climáticas e paradiplomacia ambiental do estado de São Paulo. - Farias, Valéria Cristina (2015)
The narrowing of the boundaries, presented by globalization has altered the dynamics of international relations, significantly modifying the distinctions between local and national, challenging the concepts of sovereignty, territoriality and state power. Concern about global issues was gradually being shared by stakeholders, shuffling the international scene that with the development of global governance, began to live, increasingly, in the presence of other actors, including sub-national governments that are not recognized by public international law. This study analyzed the participation of subnational governments at the International Climate Change Regime, focusing on the performance of the state of São Paulo, to try to verify the relevance of the maintenance and success of the regime, its effective capacity to action and to what extent approaches or distance of the national foreign policy. To develop the research, international regimes and particularly climate change were studied, global governance, paradiplomacy and its legal regulation in the domestic law and international law, to finally analyze how the state of São Paulo is projected on the international stage and if there is legal certainty for such action. The study revealed that the work is relevant to the maintenance of the International Climate Change Regime and to fulfill the commitments made by Brazil, concluding that paradiplomacy it lacks legal recognition, is justified in itself and in the exercise of global governance by incorporating If the international system by the emand for capacity and multilevel cooperation of sub-agents. The internal administrative structure, regulation of their paradiplomatic activity and the scale of international renown may suggest that the state of São Paulo brings together all the conditions necessary to develop federative foreign policy, but regardless of whether the already consolidated insertion through bottom-up approach, even It was within the national project, conforming with the bonds of the Brazilian federal pact, detached from the realities and needs of subnational entities.